Letter From the Editors - Rob P. Butters; Viola Vaughan-Eden (Journal of Forensic Social Work, 2011)
We are excited to welcome you the inaugural issue of theJournal of Forensic Social Work. The Journal is a forum for practitioners, scholars, policy makers, advocates, and others interested in social work in the legal system. As editors of the Journal of Forensic Social Work, our goal is for the journal to serve as a guide for social workers practicing in the forensic arena by offering them a clear identity and the knowledge base they need to practice effectively. We envision that the Journal of Forensic Social Work will serve as a primary resource for practitioners in the field of forensic social work. The journal will provide an opportunity for the discussion of important policy and social justice issues within forensic practice as well as the dissemination of empirical research on legal issues, systems of care, and on the management and treatment of victims of crime and criminal offenders. The Journal of Forensic Social Work recognizes that social workers are fundamental stakeholders in the justice system. The Journal articles will offer current theory, cutting edge research, and practice guidelines that will contribute to effective and ethically informed practice for these stakeholders. In this inaugural issue, a broad range of topics are discussed by eminent scholars such as NASW social work pioneer Dr. Carlton Munson’s article on standards of practice and an article on expert witness testimony by the leading authority in the field, Dr. Stanley Brodsky. Dr. Tina Maschi’s article on the evolution of forensic social work anchors the inaugural issue and details therich history of the work. Two articles by forensic scholars, Dr. Wesley Churchand Dr. Susan McCarter, provide a sample of exemplary research and policy articles that we will continue to disseminate though the journal. Finally, we present a review of forensic ethics and a revision of the NOFSW Code of Ethics. The quality of the scholars and articles in this first journal provide a solid foundation for the launch of this highly anticipated journal. Launching a new journal is no easy task and we are indebted to countless individuals along the way. It really does take a village to raise a child, and the same could be said about launching a journal. Over the years, the journal has been the child of many, although three individuals stand out. These three visionaries provided vital service, wisdom, and unwavering faith and without each of them, the journal would still be in its infancy. First, Dr. Ira Neighbors will be honored as the Founding Editor for his passion and grassroots work to transition the journal from an idea to a reality. Next, our consulting editor, Dr. Jon Conte, provided invaluable wisdom and consultation to bring the Journal to publication. Finally, we are indebted to Kathryn Rutz, Acquisitions Editor at Taylor and Francis, for her leadership and belief in the Journal. This is an exciting time for forensic social workers who have been waiting for a peer-reviewed publication that will promote our professional image and provide a scholarly venue for debate and the progression of knowledge. The Journal of Forensic Social Work will disseminate information based on solid research methodology, good multicultural practice, and the advancement of restorative justice and therapeutic jurisprudence that we know can ameliorate many of the social ills and crime problems in America.